Serodiagnosis and Risk Factors Associated with Infectious Agents of Reproductive Diseases in Bovines of Chiquinquirá, District of Boyacá (Colombia) - Deisy J. Lancheros-Buitrago; Diana M. Bulla-Castañeda; Martin O. Pulido-Medellin; Henry A. López Buitrago; Adriana M. Díaz-Anaya; Diego J. Garcia-Corredor (Veterinary Medicine International)
The productivity of cattle farms is affected by infectious and noninfectious factors that generate economic losses and cause reproductive failure represented by low conception rates, embryonic mortality, abortions, and fetal mummification. The infectious agents that most impact the reproductive health of the bovine species from conception to birth are bovine herpesvirus type 1 (BoHV-1) causing infectious bovine rhinotracheitis (IBR), bovine viral diarrhea virus (BVDV), bovine parainfluenza virus type 3 (PI3), Neospora caninum and Leptospira spp. The objective of this study was to diagnose the presence of BoHV-1, bovine viral diarrhea (BVD), PI3, Neospora caninum, and Leptospira spp. by serology and identify the risk factors associated with infectious agents of reproductive interest in bovines of Boyacá (Colombia). A descriptive cross-sectional study was developed, with simple random sampling, where a sample size of 601 female cattle of Holstein, Jersey, and Normande breeds of different age groups was determined. Blood samples were taken and processed using the indirect ELISA technique (SYNBIOTICS®, SERELISA® BVD p80 Ab Mono Blocking, Ingezim R.12.NC.K, PRIMACHECK VPI-3®) and the MAT test for the diagnosis of bovine leptospirosis. The data were processed with the statistical program Epi Info™. The highest apparent seroprevalence was established for infectious bovine rhinotracheitis (61.1%), followed by BVD (37.6%), PI3 (40.9%), neosporosis (51.1%), and leptospirosis (14.8%). Variables such as age >4 years and Holstein breed for IBR and >4 years for BVD were established risk factors. Considering our results, we suggest implementing prevention and control plans that include vaccination as a prophylactic measure and biosecurity tools that reduce the probability of contagion and transmission of pathogens.